Electroconvulsive Therapy Part II: A Biopsychosocial Perspective - Payne, Nancy A. (2009)
The myths surrounding electroconvulsive therapy (ECT) and the misconceptions held by the general public, clinicians, and patients have interfered with acceptance of this treatment throughout its history. Misunderstandings surrounding ECT, and its consequent stigmatization, are reviewed, including negative depictions of ECT in film, print media, and on the Internet. Clinicians involved in the delivery of ECT benefit from gaining an understanding of how ECT may be perceived by patients and other mental health professionals; they can play a vital role in educating patients and helping ensure the delivery of a successful course of ECT. Guidance is provided for clinicians on how to support patients and families through the ECT process using a model team approach. Anxiety reduction, meeting individual needs, patient and family psychoeducation, assessment of psychosocial supports, and discharge planning are discussed.